Fibroblast Growth Factor 21 in Patients with Acromegaly - Halupczok-Żyła, Jowita; Jawiarczyk-Przybyłowska, Aleksandra; Skrzypski, Marek; Strowski, Mathias Z.; Bolanowski, Marek (Experimental and Clinical Endocrinology & Diabetes, 2017)
Introduction The goal of the study was to investigate fibroblast growth factor-21 (FGF-21) levels in acromegalic patients in relation to the disease activity and to compare them with controls. Further, we aimed to evaluate the associations between FGF-21 and random growth hormone (GH), insulin-like growth factor-1 (IGF-1), metabolic and anthropometric parameters.Materials and methods The study group consisted of 50 acromegalic patients divided into 3 subgroups on the basis of disease activity (AA – active acromegaly, CD – controlled disease, CA – cured acromegaly). 27 subjects were assigned to the control group (CG). Blood samples were obtained from all participants to assess FGF-21, GH, IGF-1, lipids, glucose and insulin levels. Body mass, body mass index and body composition were also evaluated.Results There were no statistically significant differences in FGF-21 concentrations across all groups despite of subjects classification. FGF-21 correlated positively with random GH in the groups: CA, CD+CA, AA+CD+CA (r=0.48, p=0.049; r=0.39, p=0.023; r=0.33, p=0.02; respectively); with IGF-1 in the AA+CD+CA group (r=0.29, p=0.041); with triglycerides in the following groups: CD, CD+CA, AA+CD+CA (r=0.63, p=0.08; r=0.44, p=0.01; r=0.37, p=0.007; respectively) and with age in the CG and CD+CA groups (r=0.41, p=0.029; r=0.42, p=0.029; respectively). There were statistically significant negative correlations between FGF-21 and HDL-cholesterol levels in the groups: CD, CD+CA, AA+CD+CA (r=-0.53, p=0.03; r=-0.37, p=0.032; r=-0.29, p=0.036, respectively).Conclusions FGF-21 levels were similar in patients with acromegaly compared to controls. However, our results indicate that FGF-21 may have a potential role in the development of acromegaly complications.
Keywords: FGF-21; acromegaly; GH; IGF-1; body composition